Fear of crime and terrorism among backpackers: is there a relationship between country of origin and trip location? - Shechory Bitton, Mally (International journal of offender therapy and comparative criminology, 2024)
This study aimed to compare fear of terrorism and fear of crime among backpackers and investigate the differences between Israeli and Western backpackers. A cross-sectional questionnaire was administered to 120 Israeli backpackers and 109 backpackers from Western countries. Findings showed no significant differences in fear of crime between the groups, with 40% reporting exposure to crime in their home country. Israeli backpackers had higher exposure to terrorism events. While most backpackers did not experience harm during their trip, they reported higher levels of fear of crime while traveling. Israeli backpackers expressed greater fear of terrorism in their home country, while the Western group reported higher fear levels during their trip. These findings suggest the need for safer messaging and the provision of anti-crime and anti-terror information by tourism industry stakeholders and government agencies. Further research is required, particularly in understanding the impact of terrorism on travelers from diverse backgrounds.